2020
DOI: 10.1111/ijlh.13264
|View full text |Cite
|
Sign up to set email alerts
|

Cross‐evaluation of five slidemakers and three automated image analysis systems: The pitfalls of automation?

Abstract: Introduction Automated slidemakers and stainers and digital microscopes are coupled with haematology analysers to achieve better efficiency and cost‐effectiveness. This study evaluates the integrated performance of slidemakers and digital microscopes commonly available on the market. Methods We compared the percentage of neutrophils for five slidemakers (two Siemens Advia Autoslides, a SysmexSP‐10 and SP‐50 and an Abbot Alinity hs) and a Horiba Hemaprep to the corresponding haematology analyser data (Siemens A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 16 publications
(44 reference statements)
5
10
0
Order By: Relevance
“…For cell identification performance of MC-80, our study revealed good agreement between pre-and postclassification for most cell classes with excellent specificity at above 95% for all cell classes, which is comparable with various image analyzer models as reported by several studies. 6,7,[9][10][11]19,21 Interestingly, poor performance for some cell classes, for example, band neutrophils and immature granulocytes, which were consistently described in many reports regardless of the analyzer model or statistics, are also found in this study. 6,7,[9][10][11]21 The excellent sensitivity is found in most cell classes (more than 95% sensitivity) but not for blast cells (86.1%), immature granulocytes (83.1%), and reactive lymphocytes (79.6%).…”
Section: R E T R a C T E Dsupporting
confidence: 78%
“…For cell identification performance of MC-80, our study revealed good agreement between pre-and postclassification for most cell classes with excellent specificity at above 95% for all cell classes, which is comparable with various image analyzer models as reported by several studies. 6,7,[9][10][11]19,21 Interestingly, poor performance for some cell classes, for example, band neutrophils and immature granulocytes, which were consistently described in many reports regardless of the analyzer model or statistics, are also found in this study. 6,7,[9][10][11]21 The excellent sensitivity is found in most cell classes (more than 95% sensitivity) but not for blast cells (86.1%), immature granulocytes (83.1%), and reactive lymphocytes (79.6%).…”
Section: R E T R a C T E Dsupporting
confidence: 78%
“… 14 Moreover, its performance depends on the quality of the smear to adequately choose the correct reading area with the proper repartition of cells. 7 , 8 , 15 , 38 , 39 …”
Section: Discussionmentioning
confidence: 99%
“…14 Moreover, its performance depends on the quality of the smear to adequately choose the correct reading area with the proper repartition of cells. 7,8,15,38,39 By combining the advantages of flow cytometry and microscopy, IFC is a highly suitable technology for RBC evaluation. Indeed, it is a high throughput technology capable of acquiring up to a thousand events per second.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations